If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H(x) = 6x + 2 Multiply H * x xH = 6x + 2 Reorder the terms: xH = 2 + 6x Solving xH = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6x + xH = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 -6x + xH = 2 + 0 -6x + xH = 2 Reorder the terms: -2 + -6x + xH = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -6x + xH = 0 The solution to this equation could not be determined.
| H+1=28.80 | | (-2x^3+x)+(3x-6)= | | 3y+6=5y+2 | | 2-m/2 | | 275=x-(3/100) | | (45x-15)/5 | | 3x^2-14x+18=3 | | 9x+2+17x+1=13x-18+17x+1 | | 2t+10=4t-50 | | -8x+-21= | | 4(3x+11)=2.8(16+4x) | | 2-m/21 | | 8x+-21= | | -2x-6=6+2x | | k/-10=3 | | 2t-10=4t-50 | | x*x+38=2x | | 2/3t-9 | | 14g-4=2(7g-2) | | -8x+10+11= | | 4(3x+11)=2.35(16+4x) | | 6x-8x+6=-4x | | 4(3x+11)=2.45(16+4x) | | 1=r/25 | | 5+8(y-4)=5(y+2)-y | | 180(n-2)/n | | [2c+6]+3[c+8]= | | 4+3(x-2)=20 | | 4(3x+11)=3.666(16+4x) | | 4(3x+11)=-3.6(16+4x) | | (X)=2x-7 | | 6n+7-2n-14=4n+18 |